Educational Synergy of PKBM Gemilang Mandiri and Kampus Al-Qur'an Widya Silahudin Sidiq in Bogor Regency - WIDIYA, Sri (PT Batara Swastika Harati, 2024)
This study aims to examine the educational synergy between PKBM Gemilang Mandiri and Kampus Al-Qur'an in a free school program designed to enhance the academic abilities and skills of the community in Bogor Regency. The method used in this research is a qualitative approach, with data collection techniques including interviews, observations, and documentation studies. The results show that the collaboration between PKBM Gemilang Mandiri and Kampus Al-Qur'an not only increases access to education for the community but also positively impacts improving the quality of education, both in academic aspects and practical skills. This program has raised awareness about the importance of education among the local community and encouraged the active participation of older learners in the learning process. Recommendations from this study include the need for further development of educational programs involving the community and the enhancement of supporting facilities at the location. This synergy is expected to serve as a model for other free education initiatives in various regions.